2022
DOI: 10.12973/ejels.2.1.1
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Self-Efficacy and Classroom Management: Perceptions, Practices and Reflections on Professional Learning and Development

Abstract: <p style="text-align: justify;">This paper reports the findings of an investigation into English as a foreign language (EFL) teachers’ self-efficacy and their classroom management in the context of the Mekong Delta of Vietnam. The paper also aims to find out what makes teachers different in terms of skills in classroom management. The study was designed as a descriptive mixed-methods one, using a questionnaire, focus group interviews, and classroom observations to collect data. Forty-six EFL teachers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…EFL instructors in the current study were also found to value instructors' background in terms of experience and professional background, which was in line with previous research (Lap, Lien, & Thao, 2022). Most of the participants in the present study attributed their use of successful coping strategies with challenges to their experience (Shohani, Azizifar, & Kamalvand, 2014;Yerli Usul & Yerli, 2017) and less often to inborn abilities, talents, or intuitions.…”
Section: Discussionsupporting
confidence: 89%
“…EFL instructors in the current study were also found to value instructors' background in terms of experience and professional background, which was in line with previous research (Lap, Lien, & Thao, 2022). Most of the participants in the present study attributed their use of successful coping strategies with challenges to their experience (Shohani, Azizifar, & Kamalvand, 2014;Yerli Usul & Yerli, 2017) and less often to inborn abilities, talents, or intuitions.…”
Section: Discussionsupporting
confidence: 89%
“…It was indicated that pre-service language teachers agreed that this course was of very high quality. Trinh et al (2022) examined EFL teachers' self-efficacy and their classroom management in the Mekong Delta. This study employed a mixed methods design including a questionnaire, interviews, and classroom observations.…”
Section: Pre-service Teachers' Perception Of Teaching Competency Deve...mentioning
confidence: 99%
“…Previous studies have often focused predominantly on language acquisition and proficiency, with less emphasis on how educators can effectively integrate cultural elements into their teaching practices (Little, 2022;Yen et al, 2024). Given Vietnam's ongoing efforts to align its educational objectives with global standards (Lap et al, 2022;Le, 2023;Thao & Mai, 2022), this study's focus on integrating CA within EFL education addresses a critical need in the Vietnamese tertiary education landscape. This need arises from the limitations of previous research which has not sufficiently explored the intertwining of language proficiency with cultural understanding, particularly in the Vietnamese context (Phuong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%